How Much Do They Know? Oral Hygiene Attitude and Periodontal Awareness in Iraqi Adults - Alanbari, Basma F (Journal of Baghdad College of Dentistry, 2017)
Background: The scarce literature regarding oral hygiene attitude and periodontal awareness in Iraqi adults warranted the conduction of this study in order to provide a public profile and a baseline data for further researches. Aims of the study: assessing the oral hygiene attitude and periodontal awareness in a sample of Iraqi adults.Materials and Methods: Self-administered questionnaires were distributed to 500 adults.Results: Out of the 500 questionnaires distributed, 482 were included in the study.92% of the sample practiced tooth brushing, 69% out of them reported a daily brushing pattern with variable frequency,69% of the sample did not receive oral hygiene education from any source ,more than half of the sample 60 % used the horizontal brushing method, interdental aids was utilized by 42% of the sample with the dental floss being the commonest type 52%, mouthwash used by 37% and tongue cleaning was uncommon as only 22 % of the sample perform it. 78% of the sample did not know what dental plaque is while dental caries were well known by almost the entire sample 98%. 93% reported having gingival bleeding with only 5% out of them referred to the poor oral hygiene as the causative factor. The motive for seeking periodontal therapy for 80% of the sample was restoring the gingival esthetics.Conclusions: The public periodontal awareness and knowledge is still poor in Iraq, the solution requires shared resources and multiple approaches.